NURSING CARE FOR MS. Y WITH SELF-CARE DEFICIT WITH FOCUS ON TOOTH BRUSHING ACTIONS AT DR. R. M SOEDJARWADI MENTAL HOSPITAL, KLATEN - Hanif, Talitha Salsabila Putri (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Background: Mental disorders are conditions that affect a person's emotions, thought patterns, and behavior that can interfere with activities and social interactions. WHO (2022) notes that around 24 million people worldwide experience mental disorders, where more than 60% of sufferers experience self-care deficits. Self-care deficit is a condition when a person is unable to care for themselves optimally, this has a major impact on the individual's social and self-care functions, including in personal hygiene activities such as brushing their teeth. Where around 45% of patients with self-care deficits show reluctance to brush their teeth which increases the risk of oral disease and other systemic infections. Brushing teeth in patients with self-care deficits is needed to improve oral hygiene and the patient's ability to care for themselves personally. Objective: To determine nursing care from assessment to evaluation in miss Y with self-care deficits with a focus on brushing teeth. Method: The method used is the case study approach method. Results: After nursing care was carried out on miss Y with self-care deficits, it was proven to increase the miss Y's self-care ability, especially brushing their teeth. Conclusion: The act of brushing teeth is effective in increasing self-care awareness in miss Y with self-care deficits.